Archaeology and the Creag nan Uamh bone caves, Assynt, Highland - Saville, Alan (Proceedings of the Society of Antiquaries of Scotland, 2006)
Excavations in the 1920s at the Creag nan Uamh bone caves, near Inchnadamph, aroused considerable interest in the possibility of evidence for a Palaeolithic presence in north-west Scotland. Four objects found during those excavations, including the one on which the principal claim for a Palaeolithic date was based, are published here for the first time. The author contends that two are probable Viking Age/early medieval artefacts of unusual type, one is undated but is possibly also of the same period, and the fourth, while almost certainly of the Pleistocene age, is regarded as an unmodified natural object. It is argued that collectively these items serve to discount previous claims for Palaeolithic human presence. Radiocarbon dating of the human skeletal remains found, however, suggests the caves were a burial place in the Neolithic period. The paper makes extensive use of archive documentation to put the 1920s discoveries at Creag nan Uamh and their aftermath into historical context. Includes